2022
DOI: 10.7150/ijbs.69134
|View full text |Cite
|
Sign up to set email alerts
|

USF1-ATRAP-PBX3 Axis Promote Breast Cancer Glycolysis and Malignant Phenotype by Activating AKT/mTOR Signaling

Abstract: Angiotensin II type 1 receptor-associated protein (ATRAP) is widely expressed in different tissues and organs, although its mechanistic role in breast cancer remains unclear. Here, we show that ATRAP is highly expressed in breast cancer tissues. Its aberrant upregulation promotes breast cancer aggressiveness and is positively correlated with poor prognosis. Functional assays revealed that ATRAP participates in promoting cell growth, metastasis, and aerobic glycolysis, while microarray analysis showed that ATRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…AKT, belonging to the serine/threonine kinase family, is a proto-oncogene that can mediate cancer cell ferroptosis and glycolysis ( 47 , 48 ). STAT3 is an important transcription factor that also participates in the ferroptosis and glycolysis of tumor cells ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…AKT, belonging to the serine/threonine kinase family, is a proto-oncogene that can mediate cancer cell ferroptosis and glycolysis ( 47 , 48 ). STAT3 is an important transcription factor that also participates in the ferroptosis and glycolysis of tumor cells ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…33 On the other hand, it has also been shown that inhibition of MXI1 could suppress HIF-2α-dependent renal cancer tumorigenesis. 34 USF1 has been found to have a promoting effect in many types of cancers, 35,36 although its role in renal cancer has not been investigated. Interestingly, MXI1, as a repressor of the c-myc promoter, can reverse the activation of USF.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed that ERN1 knockdown in glioma cells removes the up-regulation of PAX6 and PBXIP1 genes expression introduced by glutamine deprivation and enhances the sensitivity of PBX3 gene expression to this experimental condition. The functional significance of these changes in the expression of PAX6, PBX3, PBXIP1, and MEIS2 genes, which preferentially have diverse impacts on cell proliferation and tumor growth, is under glutamine deprivation condition possibly connected with glutamine deficiency mediated by ERN1 (Auf et al 2010;Zha et al 2014;Li et al 2016Li et al , 2021Khumukcham and Manavathi 2021;Minchenko et al 2021;Wen et al 2021;Wang et al 2022). It is also possible that the endoplasmic reticulum stress mediated by ERN1 creates the resistance to glutamine deprivation and that ERN1 blockade lowers this resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of this protein markedly enhances neuroblastoma cell proliferation, anchorage-independent growth, and tumorigenicity (Zha et al 2014) and inhibits the proliferation and promotes apoptosis of thyroid cancer cells (Wen et al 2021). MEIS proteins are involved in the transcriptional regulation of PAX6 (paired box 6) and PBX proteins, which also participate in the tumorigenesis (Li et al 2016;Ooki et al 2018;Khumukcham and Manavathi 2021;Wang et al 2022). There are data indicating that inhibition of PAX6 transcripts leads to a decline in cell growth and survival and that the transcription factor PBX3 (PBX homeobox 3) promotes tumor cell growth through transcriptional suppression of the tumor suppressor p53 (Mascarenhas et al 2009;Li et al 2021).…”
mentioning
confidence: 99%